A structural and functional study of Gln147 deamidation in αA-crystallin, a site of modification in human cataract. (August 2017) - Ray, Nicholas J.; Hall, Damien; Carver, John A.
Abstract: Deamidation of Glu147 in human αA-crystallin is common in aged cataractous lenses (Hains and Truscott, Invest. Ophthalmol. Vis. Sci. 2010, 51, 3107). Accordingly, this modification may have a causative effect in cataract. αA-crystallin is a small heat-shock molecular chaperone protein that prevents aggregation of proteins and is the principal defence against crystallin unfolding and aggregation in the ageing lens. Deamidated Q147E αA-crystallin was structurally characterised using a variety of spectroscopic and biophysical methods, including NMR, circular dichroism and fluorescence spectroscopy and dynamic light scattering. The effect of Glu147 deamidation on αA-crystallin in vitro chaperone ability was determined for a variety of aggregating proteins. Compared to the wild type protein, Q147E αA-crystallin generally exhibited slightly reduced chaperone ability and a small loss of overall structure in its central α-crystallin domain while also showing significantly enhanced thermal stability and a tendency to form slightly larger oligomers. As αA-crystallin is the major lens protein, even a small loss of function could combine with other sources of age-related damage to the crystallins to contribute to lens opacification. Highlights: Q147E deamidation of αA-crystallin results in a partial loss molecular of chaperone function. Q147E deamidation of αA-crystallin causes an increase in protein thermal stability. Q147E deamidation of αA-crystallin corresponds to an increase in oligomer size.